Odor mitigation measures for an equalization tank of a Wastewater Treatment Plant in Costa Rica - Castellón, Britanny Ramos (2023)
[Objective] The objective of this study was to evaluate the short-term response of four different odor mitigation measures in a homogenization tank of a university WWTP. [Methodology] Aeration, addition of lime, addition of iron sulfate, and addition of the commercial product BiOWiSH® Odor were implemented over a study period equal to four hydraulic retention times. Monitoring was conducted for the influent water and within the tank for each period, including a baseline measurement for comparison. pH, oxidation-reduction potential, and dissolved oxygen were measured in triplicates every 30 minutes, along with the concentration of dissolved sulfide. An odor perception survey was administered to WWTP visitors, evaluating intensity, offensiveness, and character with a total of 15 surveys per period. Differences between the mitigation measures and baseline were determined using t-student tests for quantitative data and Mood's medians for qualitative data. Minitab 2019 was used with a confidence level of 95%. [Results] All the mitigation measures significantly decreased the concentration of dissolved sulfide in the tank. Aeration prevented oxygen depletion, reducing conditions, and acid fermentation, favoring the oxidation of odorous compounds. It was the only studied mitigation measure that led to a reduction in intensity and offensiveness of the odor. [Conclusions] The application of aeration induced changes in the tank's behavior and odor perception, confirming its effectiveness. The addition of iron sulfate, lime, and BiOWiSH® did not generate significant changes in odor perception.